Nutritional potentiality of earthworm (Perionyx excavatus) for substituting fishmeal used in local feed company in Bangladesh - Hasanuzzaman, A.F.Md.; Hossian, Sk.Z.; Das, M. (Mesopotamian Journal of Marine Sciences, 2022)
Nutritional composition of wild earthworm (Perionyx excavatus) and fishmeal used by local fish-feed industry in Bangladesh was determined to evaluate the nutritionally replacement potentiality of this earthworm species for fishmeal mostly used in feed for aquaculture and other animal production. Except for moisture content, the proximate chemical values in P. excavatus did not differ significantly (P≥0.05) from that in fishmeal. On an average, the earthworm had lower protein content (46.57 ± 0.97%) than fishmeal had (54.97 ± 7.49 %). On the other hand, the mean lipid content (8.03 ± 0.44 %) in this earthworm was found to be higher compared to fishmeal (7.97 ± 1.60 %). The average ash content in the earthworm and fishmeal were 24.26 ± 0.68 % and 24.13 ± 8.44 %, respectively. The results of the present study indicate that this earthworm species had almost similar nutritional values to the fishmeal, and thus would be a potential source of animal protein in supplementing fishmeal. In an implication, year-round production of this earthworm species through standard mass culture system, and its radical use could play a pivotal role in sustainable fisheries and aquaculture production.